2005
DOI: 10.1007/s00520-005-0864-x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of a multidimensional exercise intervention on physical capacity, well-being and quality of life in cancer patients undergoing chemotherapy

Abstract: The aim of the present study was to investigate the impact of a multidimensional exercise intervention focusing on physical capacity; one-repetition maximum (1RM) and maximum oxygen uptake (VO2Max), activity level, general well-being and quality of life in cancer patients undergoing chemotherapy. The intervention comprised resistance and fitness training, massage, relaxation and body-awareness training. Eighty-two cancer patients, with or without evidence of residual disease, were included: 66 patients with 13… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
120
1
2

Year Published

2007
2007
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(132 citation statements)
references
References 60 publications
2
120
1
2
Order By: Relevance
“…Physical activity has become an important part of postcancer treatment as a rehabilitation tool for improving general well-being and increasing physical fitness through a significant reduction of treatment-related symptoms [2]. Especially physical fitness, psychological, and social well-being enable young athletic patients with cancer to regain control and form a strong cancer identity [1].…”
Section: Introductionmentioning
confidence: 99%
“…Physical activity has become an important part of postcancer treatment as a rehabilitation tool for improving general well-being and increasing physical fitness through a significant reduction of treatment-related symptoms [2]. Especially physical fitness, psychological, and social well-being enable young athletic patients with cancer to regain control and form a strong cancer identity [1].…”
Section: Introductionmentioning
confidence: 99%
“…Also in the second outcome Physical Performance Test used for measuring physical performance showed significant improvement in the experimental group, this can be supported by the study of Adamsen et al (2006) where they observed highly significant improvements in physical functioning (p<0.001) and role functioning (p<0.001) after a multidimensional exercise intervention on physical capacity, well-being and quality of life in cancer patients undergoing chemotherapy. Regarding the exercises along with relaxation techniques has significant effect as because after chemo there are many side effects like severe fatigue and reduced strength etc.…”
Section: Resultsmentioning
confidence: 58%
“…The diagnosis of CA is a strong impact, reduces life expectancy and increases depression level in about 25% of the patients, being depression also related to the use of corticosteroids used in the treatment (2) . During the course of the treatment, the patients experience review article EXERCISE AND SPORTS MEDICINE CLINIC many collateral effects, which include: astenia, ataxia, anemia, anxiety, nausea, vomiting, diarrhea, sarcopenia, osteopenia, mood swings, neutropenia, body composition and perceotion alteration, thrombopenia, decrease in flexibility, sleep disorders, self-esteem reduction, depression, cardiopulmonary and vascular function reduction, pain and fatigue (5)(6)(7) , and these effects can persist for months or even years after the end of the treatment (5,8) .…”
Section: Resultsmentioning
confidence: 99%
“…Due to the exercise particularity and complexity, a multidimensional approach which included resistance and aerobic exercises, relaxation, body awareness, massage and flexibility would be broader, since it would provide a more holisti approach (6,17,18) . Although it is not known yet which approaches are more efficient over others (19) , the massive majority of the investigations use aerobic exercises of moderate intensity as a therapeutic method (3)(4)(5)10,16,18,20) .…”
Section: Exercise Typesmentioning
confidence: 99%